Distribution and Prevalence of Serotypes of Group B Streptococcus Isolated from Pregnant Women in 30 Countries: A Systematic Review. Issue 2 (26th April 2023) - Maria Silva, Marta; Alcântara Silva, Érica; Novais Teixeira Oliveira, Caline; Cordeiro Santos, Maria Luísa; Lima Souza, Cláudio; Freire de Melo, Fabrício; Vasconcelos Oliveira, Márcio
Abstract: Objective: This review aimed to compile scientific data on the distribution and prevalence of group B Streptococcus (GBS) serotypes isolated from pregnant women across 30 countries from 2010 to 2019. Methods: This was a systematic review that addresses the distribution and prevalence of GBS in pregnant women. The search included studies published between January 2010 and December 2019 in PubMed, Virtual Health Library (BVS), ScienceDirect, Scientific Electronic Library Online (SciELO), and LILACS databases. We also surveyed relevant articles published in English, Spanish, and Portuguese between February and April 2020. Original articles, communication, short report, theses, and dissertations were included. The prevalence of GBS colonization, method for capsular serotyping, antimicrobial resistance, distribution and prevalence of serotypes were extracted from each study. Results: In all, 795 publications were identified. After applying the eligibility criteria, 48 articles were included for the final systematic analysis; most articles were from Asia and were published during the years 2014 to 2017. For the identification of serotypes, most studies used the polymerase chain reaction technique. There were records of all 10 GBS serotypes, namely, Ia, Ib, and II–IX, among the countries analyzed. GBS susceptibility and resistance to antibiotics were addressed in 37.5% of the publications analysed. Conclusion: This review showed that GBS serotypes are distributed differently in the 30 analyzed countries, with serotypes Ia, Ib, and II to V being the most prevalent. Furthermore, our results highlighted the relationship of GBS with maternal colonization, implications for neonates, and antibiotic resistance.